Issues & Facets of Women’s Entrepreneurship, Particularly with Regard to MSMSs in Haryana - Sharma, Shivam (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2023)
Understanding the many obstacles that make it difficult for women to follow their entrepreneurial ideas is urgently needed in the Indian state of Haryana. The goal of this study is to identify the obstacles that women entrepreneurs confront and estimate their futures through interviews with female business owners in the state of Haryana. Many factors, including family and education, are essential empowering elements that support female entrepreneurs in Haryana and help to strengthen their motivation to act within the state. There is a dearth of regional study, particularly in the state of Haryana, that was directed with a remarkable emphasis on female business visionaries in the writing of the history of business. This analysis is one of its type and will serve as a foundation for more research into the status of problems and the prospects for female entrepreneurs to continue and succeed in their entrepreneurial endeavours